Praktik Pemenuhan Nafkah Dalam Rumah Tangga (Studi Kasus di Kecamatan Anjir Pasar Kabupaten Barito Kuala) - Wati, Kurnia; Rahmi, Diana (Interdisciplinary Explorations in Research Journal, 2024)
ABSTRACT The provision of maintenance has been regulated in Islamic law and positive law.  However, not all households are able to implement it according to the provisions. This causes the Anjir Pasar community to use many other methods in fulfilling household maintenance so that they can continue to meet all the needs of their household. The purpose of this study is to describe the implementation of the fulfillment of household maintenance in the Anjir Pasar community and its impact. This research is an empirical legal research using a descriptive approach. Data were collected through observations and interviews with eight informants who came from different families and applied a variety of methods of fulfilling livelihoods that were not the husband as the sole breadwinner. Data processing techniques used editing and descriptive, and data analysis using qualitative. The results showed that there were case variations in the method of fulfilling the Anjir Pasar community's livelihood. The variations in methods in question include husbands being assisted by their wives voluntarily to fulfill their livelihoods by sharing their duties and roles, husbands and wives sharing their duties and roles towards livelihoods under the coercion of their husbands, alternating every month using the husband's and wife's income, purely using the wife's income, using children's income, using the results of joint efforts of husband and wife, using fees from the husband's parents, and using the income of each husband and wife. The impact of these methods is that three families have fulfilled their right to maintenance and the household is harmonious, three families have not fulfilled their right to maintenance and the household is not harmonious, one family has not fulfilled their right to maintenance but the family remains harmonious and one family is divorced. Keywords: Fulfillment, Maintenance, Household   Abstrak Ketentuan nafkah telah diatur dalam hukum Islam dan hukum positif.  Tetapi, tidak semua rumah tangga mampu melaksanakannya sesuai ketentuan. Hal ini menyebabkan masyarakat Anjir Pasar menggunakan banyak metode lain dalam pemenuhan nafkah rumah tangga agar bisa tetap memenuhi segala kebutuhan dalam rumah tangganya. Tujuan penelitian ini untuk menggambarkan pelaksanaan pemenuhan nafkah dalam rumah tangga pada masyarakat Anjir Pasar beserta dampaknya. Penelitian ini adalah penelitian hukum empiris dengan menggunakan pendekatan deskriptif. Data dikumpulkan melalui observasi dan wawancara kepada delapan orang informan yang berasal dari keluarga yang berbeda dan menerapkan variasi metode pemenuhan nafkah yang bukan suami sebagai pemenuh nafkah satu-satunya. Teknik pengolahan data menggunakan editing dan deskriptif, serta analisis data menggunakan kualitatif. Hasil penelitian menunjukkan adanya variasi kasus dalam metode terhadap pemenuhan nafkah masyarakat Anjir Pasar. Variasi metode yang dimaksud seperti suami dibantu istri dengan sukarela untuk memenuhi nafkah dengan cara berbagi tugas dan peran masing-masing, suami istri berbagi tugas dan peran terhadap nafkah atas paksaan suami, bergantian setiap bulan menggunakan penghasilan suami dan istri, murni menggunakan penghasilan istri, menggunakan penghasilan anak, atas hasil usaha bersama suami istri, menggunakan biaya dari orang tua suami, dan menggunakan penghasilan masing-masing suami istri. Dampak yang dihasilkan dari metode-metode tersebut adalah tiga keluarga hak nafkahnya terpenuhi dan rumah tangga harmonis, tiga keluarga hak nafkahnya tidak terpenuhi dan rumah tangganya tidak harmonis, satu keluarga hak nafkahnya tidak terpenuhi tetapi kelurga tetap harmonis dan satu keluarga bercerai. Kata Kunci : Pemenuhan, Nafkah, Rumah Tangga